2001
DOI: 10.1073/pnas.98.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Activation of calcium entry in human carcinoma A431 cells by store depletion and phospholipase C- dependent mechanisms converge on ICRAC-like calcium channels

Abstract: Activation of phospholipase C in nonexcitable cells causes the release of calcium (Ca 2؉ ) from intracellular stores and activation of Ca 2؉ influx by means of Ca 2؉ release-activated channels (ICRAC) in the plasma membrane. The molecular identity and the mechanism of I CRAC channel activation are poorly understood. Using the patch-clamp technique, here we describe the plasma membrane Ca 2؉ channels in human carcinoma A431 cells, which can be activated by extracellular UTP, by depletion of intracellular Ca 2؉ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
7
27
0
Order By: Relevance
“…TRPC3 Does Not Regulate I min and I max Cation ChannelsWe have previously shown that A431 cells express highly selective I min calcium channels that could be activated by extracellular UTP, intracellular InsP 3 and depletion of intracellular Ca 2ϩ stores (35,36,39, see also Fig. 5F).…”
Section: Suppression Of Trpc3 Expression Reduces Store-operatedmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPC3 Does Not Regulate I min and I max Cation ChannelsWe have previously shown that A431 cells express highly selective I min calcium channels that could be activated by extracellular UTP, intracellular InsP 3 and depletion of intracellular Ca 2ϩ stores (35,36,39, see also Fig. 5F).…”
Section: Suppression Of Trpc3 Expression Reduces Store-operatedmentioning
confidence: 99%
“…We found that I SOC currents are at least partly mediated by I min channels, whose activity is controlled by downstream products of PLC (33)(34)(35)(36)(37)(38) and could be triggered by passive depletion of intracellular Ca 2ϩ stores with Tg and/or BAPTA-AM (39). In the present study, we aimed to determine the role of TRPC3 in mediating the receptor-and store-operated calcium influx in A431 cells.…”
mentioning
confidence: 99%
“…Several studies also have suggested that Trp3 activation involves interaction with underlying IP 3 Rs or, in some instances, ryanodine receptors (34)(35)(36). There is also evidence that CCE may involve such an interaction (37,38), in support of the proposed conformational coupling model for the regulation of SOCs (7,8). Thus, despite the fact that expressed Trp3 apparently is not regulated by store depletion, its interaction with IP 3 Rs has been investigated as a model for understanding the conformational coupling mechanism.…”
mentioning
confidence: 99%
“…I min Channels Act as ROC Channels in HEK293 Cells-In the previous studies we utilized single channel patch clamp recordings to characterize Ca 2ϩ influx channels in A431 cells (13)(14)(15)(16)(17)(18)(19). What are the channels supporting Ca 2ϩ influx in HEK293 cells?…”
Section: Store-operated Andmentioning
confidence: 99%
“…We reasoned that single channel patch clamp recordings provide unique and precise information about functional properties of individual types of channels supporting Ca 2ϩ influx in non-excitable cells. In our previous experiments we used single channel patch clamp recordings to perform detailed characterization of channels supporting Ca 2ϩ influx in A431 cells (13)(14)(15)(16)(17)(18)(19)). Now we extended our studies to HEK239 cell line, which is used extensively as heterologous expression host in functional studies of TRPC family members, such as TRPC1 (20), TRPC3 (21-23), TRPC4 (24), TRPC5 (20,23,25), TRPC6 (26,27), and TRPC7 (27).…”
Section: Activation Of Phospholipase C (Plc)mentioning
confidence: 99%